Implementasi Kehidupan Moderasi Beragama di Padangsidimpuan - Nasution, Syafri Martabe; -, Maimunah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Padangsidimpuan, located in North Sumatra Province, is a region with a high level of religious diversity, encompassing Islam, Christianity, Hinduism, and Buddhism. This diversity requires serious efforts to create a harmonious religious life. In this context, religious moderation plays an important role. This study aims to analyze the implementation of religious moderation in Padangsidimpuan, focusing on interfaith dialogue, the role of educational institutions, and government policies that support inclusive and harmonious religious life. Using a descriptive qualitative method, this research gathers data through interviews with religious leaders, government officials, and the community, as well as direct observations of social interactions between religious groups. The findings show that the implementation of religious moderation in Padangsidimpuan is reflected in regular interfaith dialogues, the active role of educational institutions in instilling values of tolerance, and government support in facilitating interfaith social activities. Although there are challenges, such as limited understanding of religious moderation among some segments of society, the efforts made show positive results in maintaining interreligious harmony. This study is expected to contribute to the development of more inclusive policies and strengthen harmonious religious life in other regions with similar diversity.